1998
DOI: 10.1128/jcm.36.10.3007-3012.1998
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Candida dubliniensis in Oropharyngeal Samples from Human Immunodeficiency Virus-Infected Patients in North America by Primary CHROMagar Candida Screening and Susceptibility Testing of Isolates

Abstract: Candida dubliniensis has been associated with oropharyngeal candidiasis in patients infected with human immunodeficiency virus (HIV). C. dubliniensis isolates may have been improperly characterized as atypical Candida albicans due to the phenotypic similarity between the two species. Prospective screening of oral rinses from 63 HIV-infected patients detected atypical dark green isolates on CHROMagar Candida compared to typical C. albicans isolates, which are light green. Forty-eight atypical isolates and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
116
4
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(143 citation statements)
references
References 18 publications
16
116
4
7
Order By: Relevance
“…9 In 1995, Sullivan et al 10 recovered form AIDS patients a new species of Candida, namely, C. dubliniensis differing from C. albicans in certain phenotypic and molecular characteristics. Candida dubliniensis has been reported from oropharyngeal samples of patients with advanced AIDS having mean CD4 cell counts <50 mm 3,10,11 but this emerging yeast has not been reported hitherto from Indian patients.…”
Section: Introductionmentioning
confidence: 99%
“…9 In 1995, Sullivan et al 10 recovered form AIDS patients a new species of Candida, namely, C. dubliniensis differing from C. albicans in certain phenotypic and molecular characteristics. Candida dubliniensis has been reported from oropharyngeal samples of patients with advanced AIDS having mean CD4 cell counts <50 mm 3,10,11 but this emerging yeast has not been reported hitherto from Indian patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although the C. dubliniensis isolates examined did not assimilate a-methyl-D D-glucoside, xylose and DL DL-lactate such non-assimilation is again regarded as a typical property of C. dubliniensis (Gales et al 1999;Pincus et al 1999;Giammanco et al 2000) and the biocode obtained (vide supra) is typical of C. dubliniensis (Giammanco et al 2000;Sullivan et al 1997). In some studies, C. dubliniensis has been differentiated on CHROMagar Candida based on the production of dark green colonies compared with the lighter green colonies of C. albicans (Kirkpatrick et al 1998). However, others have not been able to differentiate C. dubliniensis from C. albicans isolates by the colour of colonies (Tintelnot et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…to grow at 45°C and Kirkpatrick et al [25] reported an even higher percentage of C. albicans isolates (36%) that failed to grow at this temperature. Pincus et al [20] stated that these variable results may be explained by poor temperature control in incubators or differences in media composition.…”
Section: Growth At Elevated Temperaturesmentioning
confidence: 98%
“…Similarly, Kurzai et al [18] found that characteristic chlamydospore formation on rice-Tween agar was only observed in 57% of C. dubliniensis isolates and concluded that this characteristic cannot be used for accurate identification of this species. In addition, Kirkpatrick et al [25] found that only 70% of the examined C. dubliniensis isolates produced abundant chlamydospores, while 4% of the C. albicans isolates also produced abundant chlamydospores on corn meal agar. This was confirmed by Á lvarez et al [17] who found that 13% of C. albicans isolates examined also produced abundant chlamydospores in pairs, triplets or clusters on corn meal-Tween agar.…”
Section: Chlamydospore Productionmentioning
confidence: 99%